The effect of sharia share selection based on financial ratio and corporate governance mechanism on the quality of company profit - Nida Ulya Sofana; Faris Shalahuddin Zakiy; Muchammad Fauzi; Singgih Muheramtohadi; Najim Nur Fauziah (Journal of Islamic Accounting and Finance Research, 2021)
Purpose - This study aims to obtain empirical evidence regarding the effect of Islamic stock selection based on financial ratios (debt to assets ratio, debt to equity ratio, non-halal income ratio) and corporate governance mechanisms (managerial ownership, independent commissioners, institutional ownership, audit committee) on company earnings quality.Method - The population of this research is all companies that are members of the Indonesian Sharia Stock Index in 2017-2019. The sample selection used purposive sampling method and obtained 67 sample companies. This study uses secondary data with multiple linear regression analysis method.Result - Debt to assets ratio, managerial ownership, institutional ownership, and audit committee have no significant positive effect on earnings quality. The ratio of non-halal income has a negative and significant effect on earnings quality. Meanwhile, the debt to equity ratio and independent commissioners do not have a significant negative effect on earnings quality.Implication - Companies that are members of the Indonesian Sharia Stock Index are expected to be able to improve the quality of their financial reports. On the other hand, investors are expected to find out and study the company's annual report as a material consideration for investment decisions.Originality - The originality of the research is this study intends to develop previous research by examining the selection criteria for sharia shares and corporate governance mechanisms.